PENGARUH FLUKTUASI DEBIT TERHADAP POLA FLUKTUASI KARBON DI SUNGAI SURABAYA - prihartono, prihartono (Badan Pengkajian dan Penerapan Teknologi, 2008)
Fluctuation of carbon in rivers are considered to be reflection of their rivers discharge fluctuation. To monitor carbon concentration fluctuation in Surabaya river, several water samples were analyzed automatically in Automated Water Monitoring System MERMAID (Marine, Environmental Remote-Controlled Monitoring and Integrated Detection) for Total Inorganic Carbon (TIC) and Total Organic Carbon (TOC). An inverse relationship with discharge was found in this study, relatively high TIC and TOC observed at low discharge and low TIC and TOC in high discharge. It shows dilution process of carbon organic and inorganic during rainy seasons and accumulation process during dry seasons. Inorganic carbon (TIC) is the dominant form of carbon transport in Surabaya river. The high amount of inorganic suggesting basin-wide flushing with dominant allochthonous HCO3 - from carbonate rocks regions in Brantas basin.